Mewujudkan Pendaftaran Tanah Yang Responsif Pada Era Disrupsi Sebagai Penunjang Kesejahteraan Rakyat - Zaelani, Muhammmad Aziz; Setiyawan, Wahyu Beny Mukti; Dona, Fery (JURNAL USM LAW REVIEW, 2022)
This article aims to examine the importance of realizing responsive land registration in the era of disruption to support people's welfare and examine the form of responsive land registration in the era of disruption to support people's welfare. Land registration has a high urgency because it is one of the elements in supporting the welfare of the people. This welfare is related to legal certainty and the fulfillment of governance needs which is manifested in guaranteeing legal protection for land management. However, there are still various problems related to land registration, especially in the era of disruption that demands optimization of technology. Therefore, changes are needed with responsive land registration as a solution. This article includes normative legal research with a statutory and conceptual approach. The urgency is to show a prescriptive on what should be applied to the legal issues under study, especially finding a form of land registration that is responsive in the era of disruption. The results show: (i) The urgency of realizing responsive land registration in the era of disruption to support people's welfare is that there are still land conflicts, the need for an efficient land registration mechanism and maximizing technology; (ii) Responsive forms of land registration in the era of disruption to support people's welfare are realized by: efficiency of land registration by means of information technology, optimization of responsive land registration by expanding community participation facilities, and accountability of land registration by revitalizing land stakeholders.Artikel ini bertujuan untuk mengkaji  pentingnya mewujudkan pendaftaran tanah responsif pada era disrupsi sebagai penunjang kesejahteraan rakyat, dan mengkaji tentang bentuk pendaftaran tanah responsif pada era disrupsi sebagai penunjang kesejahteraan rakyat. Pendaftaran tanah penting untuk menunjang kesejahteraan rakyat. Kesejahteraan berkaitan dengan jaminan perlindungan hukum pengelolaan tanah. Masih terdapat permasalahan pendaftaran tanah pada era disrupsi yang menuntut optimalisasi teknologi menghadapi perubahan. Diperlukan perubahan pendaftaran tanah responsif sebagai jalan keluar. Artikel ini termasuk penelitian hukum normatif, menggunakan bahan hukum primer dan sekunder, analisis deduktif dengan pendekatan perundangan serta konseptual. Hasil penelitian menunjukkan: urgensi mewujudkan pendaftaran tanah responsif pada era disrupsi sebagai penunjang kesejahteraan rakyat adalah maraknya konflik pertanahan, kebutuhan mekanisme pendaftaran tanah yang efisien dan memaksimalkan teknologi;   bentuk pendaftaran tanah responsif pada era disrupsi diwujudkan dengan efisiensi pendaftaran tanah dengan teknologi informasi, optimalisasi pendaftaran tanah responsif dengan memperluas partisipasi masyarakat, akuntabilitas pendaftaran tanah dengan revitalisasi stakeholder pertanahan.